Examining the effects of femoral anteversion and passive hip rotation on ACL injury and knee biomechanics: a systematic review and meta‐analysis - Jennifer A. Hogg; Justin P. Waxman; Sandra J. Shultz (Journal of Experimental Orthopaedics, 2022)
Abstract Purpose Greater femoral internal rotation (via anteversion or passive hip ROM) is associated with knee biomechanics thought to contribute to anterior cruciate ligament (ACL) injury, but it is unknown if femoral internal rotation contributes to actual ACL injury occurrence. The objective of this systematic review and meta‐analysis was to quantify the extent to which femoral anteversion and hip range of motion (ROM) influence knee biomechanics consistent with ACL injury and actual ACL injury occurrence. Methods Using PRISMA guidelines, PubMed, CINAHL, SportDiscus, and Scopus databases were searched. Inclusion criteria were available passive hip ROM or femoral anteversion measure, ACL injury OR biomechanical analysis of functional task. Two reviewers independently reviewed titles, abstracts, and full texts when warranted. Included studies were submitted to Downs & Black Quality Assessment Tool. Meta‐analyses were conducted for comparisons including at least two studies. Results Twenty‐three studies were included (11 injury outcome, 12 biomechanical outcome). Decreased internal rotation ROM was significantly associated with history of ACL injury (MD ‐5.02°; 95% CI [‐8.77°—‐1.27°]; p = 0.01; n = 10). There was no significant effect between passive external rotation and ACL injury (MD ‐2.62°; 95% CI [‐5.66°—‐ 0.41°]; p = 0.09; n = 9) Participants displaying greater frontal plane knee projection angle had greater passive external rotation (MD 4.77°; 95% CI [1.17° – 8.37°]; p = 0.01; n = 3). There was no significant effect between femoral anteversion and ACL injury (MD ‐0.46°; 95% CI [‐2.23°—1.31°]; p = 0.61; n = 2). No within‐sex differences were observed between injured and uninjured males and females (p range = 0.09 – 0.63). Conclusion Though individuals with injured ACLs have statistically less passive internal and external rotation, the observed heterogeneity precludes generalizability. There is no evidence that femoral anteversion influences biomechanics or ACL injury. Well‐designed studies using reliable methods are needed to investigate biomechanical patterns associated with more extreme ROM values within each sex, and their prospective associations with ACL injury. Level of evidence: IV.